Early Development Economics Debates Revisited - Alacevich, Michele ca. 20. Jh (The World Bank, 2008)
Development economics in its early years created the image of a fierce fight between advocates of contrasting theories or approaches- "balanced growth" vs. "unbalanced growth" or "program loans" vs. "project loans." This view has the merit to highlight such conflicts in great detail; yet it fails to take into account the reality of development economics as it was practiced in the field. This paper reassesses these old conflicts by complementing the traditional focus on theoretical debates with an emphasis on the practice of development economics.A particularly interesting example is the debate between Albert Hirschman, one of the fathers of the "unbalanced growth" approach, and Lauchlin Currie, among the advocates of "balanced growth" on how to foster iron production in Colombia in the 1950s. An analysis of the positions held by these two economists shows that they were in fact much less antithetical than is usually held and, indeed, were in some fundamental aspects surprisingly similar. Debates among development economists during the 1950s thus must be explained-at least partially-as the natural dynamics of an emerging discipline that took shape when different groups tried to achieve supremacy-or at least legitimacy-through the creation of mutually delegitimizing systemic theories